2007
DOI: 10.1002/jemt.20488
|View full text |Cite
|
Sign up to set email alerts
|

Polarized light imaging of white matter architecture

Abstract: Polarized light imaging (PLI) is a method to image fiber orientation in gross histological brain sections based on the birefringent properties of the myelin sheaths. The method uses the transmission of polarized light to quantitatively estimate the fiber orientation and inclination angles at every point of the imaged section. Multiple sections can be assembled into a 3D volume, from which the 3D extent of fiber tracts can be extracted. This article describes the physical principles of PLI and describes two maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 45 publications
1
107
0
Order By: Relevance
“…However, the description of nerve fiber axis orientation in 3-D requires both azimuthal and polar angles. Computational methods 37 and experimental methods utilizing measurements with variable incident angle 38,24 have been proposed to retrieve 3-D axis using PS-OCT. Quantification of the fiber inclination would allow calculation of the true birefringence Δn, since the measured apparent birefringence can be written as Δn 0 ¼ Δn cos 2 α, 39 where α is the inclination angle. Combining the information from variable incident angles after registering the 3-D datasets has potential to improve the image quality and representation of tissue anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the description of nerve fiber axis orientation in 3-D requires both azimuthal and polar angles. Computational methods 37 and experimental methods utilizing measurements with variable incident angle 38,24 have been proposed to retrieve 3-D axis using PS-OCT. Quantification of the fiber inclination would allow calculation of the true birefringence Δn, since the measured apparent birefringence can be written as Δn 0 ¼ Δn cos 2 α, 39 where α is the inclination angle. Combining the information from variable incident angles after registering the 3-D datasets has potential to improve the image quality and representation of tissue anisotropy.…”
Section: Discussionmentioning
confidence: 99%
“…The principles of 3D-PLI have been explained in detail by Axer et al (2001), Larsen et al (2007), Axer et al (2011a), andAxer et al (2011b). In this section, only the basic setup needed for the simulation approach is described.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It has been shown that 3D Polarized Light Imaging (3D-PLI) is able to reveal fiber structural details within histological sections of a postmortem human brain and to derive spatial fiber orientations for each tissue voxel (Axer et al, 2011a(Axer et al, ,2011bLarsen et al, 2007). The measurement principle of 3D-PLI relies on the birefringence of nervous tissue which is mainly caused by the regular arrangement of lipids in the myelin sheaths surrounding most nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the changes of a polarized beam of light caused by birefringent or anisotropic structures as the light passes through a sample, such as highly organized myelinated fibers in brain tissue (Larsen et al 2007). Instead of optical anisotropy, here the anisotropy refers to the organization of fibers in a single orientation described by the parallelism index.…”
Section: Polarized Light Microscopymentioning
confidence: 99%